Golden hour management of pediatric polytrauma in India- Emergency department resuscitation - Geethanjali Ramachandra; Michael Shepherd (Wolters Kluwer Medknow Publications, 2017)
Trauma is one of the most neglected preventable diseases in India, with the 2014 National Crime Records Bureau report, detailing 63% rise in injury deaths in the past decade. Despite the worrying figures, this preventable endemic has not received much attention and a significant proportion of trauma victims do not receive timely and appropriate medical care. There is often an enormous amount of anxiety and confusion in the Emergency Department (ED) when it comes to resuscitating a child with polytrauma. Emergency triage, application of algorithms of primary and secondary survey which are easily remembered and reproducible all over the world, should be applied to simplify trauma resuscitation in children. Skilled team approach during the first hour ('Golden Hour') by focussing on 3 critical 'H's - H ( Hypoxia prevention), H (Hemorrhage control) and H ( Herniation of brain prevention) could save thousands of lives and is urgently needed across India